The Sociability of Janina Degutytė’s Poetry - Satkauskytė, Dalia (Colloquia, 2018)
Janina Degutytė (1929–1990) has gone down the history of Lithuanian literature as a poet who has continued the lyrical and neo-romantic tradition of Salomėja Nėris (1904–1944), whose worldview is dominated by the intimate relationship between the individual and the world, humans and nature, and, in late poetry, the dramatics resulting from her personal life story. The article raises the questions of whether one could consider such personal lyrical poetry as sociable, or whether it is possible to examine for the seal of problems, conflicts, and imagination characteristic of the period when Degutytė created her works – the Soviet era.The stimulus and theoretical basis for this research was Theodor Adorno’s article On Lyric Poetry and Society. Social assumptions for lyrical poetry, as described by Adorno, are considered the first and most abstract layer of sociability. The author discovers the other two layers of sociability of Degutytė’s lyrical poetry by doing sociocritical analysis, where she compares the official Soviet discourse with the poetic text by observing the ways in which poetry reacts to the sociolectic situation of the Soviet era. She considers the second layer of sociability to be the traces of the Soviet discourse in a poem, such as the speaker’s enthusiasm, maximalism, cosmic perspective of the living world, and the contraposition of spirituality and materiality. The third layer is considered to be the very situation of reciting the poetry, whose basis is an intimate appeal to the other. The Soviet reader perceived it as an alternative to Soviet rhetoric.In her late poetry, along with the dramatic reflection on the relationship between mother and daughter, the poet develops the theme of social sensitivity, and intensifies her effort to give voice to the mutes of society.
Keywords: Janina Degutytė; lyrical poetry; sociocriticism; sociolectic situation; Soviet-era literature; Theodor Adorno